Influence of the parasitic series inductance of the coupling capacitor of a SEPIC to the coil current waveforms with coupled inductors - Laugner, Manuel; Eberle, Thomas (IEEE International Symposium on Industrial Electronics, 2022)
A previously neglected effect when using coupled inductors in the SEPIC is considered. It is based on the interaction of the leakage inductance with the series inductance of the coupling capacitor. This effect is evident in sudden changes of the inductor currents during the switching processes, increases the electromagnetic interferences and decreases the efficiency of the converter. The theoretical analysis shows significant impacts, especially for closely coupled inductors. The impact and therefore the filter effort can be significantly reduced by optimizing the components and the PCB-layout. The effect is verified by means of LTSpice simulations and experimental measurements of a hardware setup. It is directly transferable to other higher-order converters.
CRIS-Team Scopus Importer:2022-08-26
Keywords: coupled-inductors; CUK; current-jumps; filter; SEPIC